الميتافيزيقا والانحطاط في فلسفة نيتشه "نقد المسيحية أنموذجاً" - شباني منذر (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يتناول البحث مفهوم الانحطاط في فلسفة نيتشه، في محاولة لإبراز دور هذا المفهوم في فلسفة التاريخ لديه أولاً، ثم استخدام نيتشه لهذا المفهوم في نقده للمسيحية ثانياً، وخصوصاً أن نيتشه يرى في المسيحية نفسها انحطاطاً منهجياً عندما تمكنت من تزييف القيم ومحاربة كل طاقة إنسانية خلاّقه ، واستثمار القيم التي دعت إليها للوقوف ضد القوة والارتقاء الطبيعيين ، وأخيراً فإن البحث يتناول موقف نيتشه الداعي إلى إعادة كتابة التاريخ العام والتاريخ المسيحي الفعلي. The research handles the concept of decadence in the philosophy of Nietzsche, in an attempt to highlight the role of this concept first in Nietzsche’s the philosophy of history, then Nietzsche’s use of this concept in criticizing Christianity, as Nietzsche saw in Christianity a systematic degeneration when it falsified values ​​and fight human creativity, and invested the values which it called for them to stand against the natural power and natural progress. Finally, this research deals with Nietzsche’s attitude which calls for rewriting general history and the actual Christian history.